PENGARUH TINGKAT SUKU BUNGA DEPOSITO TERHADAP DANA PIHAK KETIGA DI BANK BJB CABANG RANGKASBITUNG - Jamaluddin; Ahmad Tabrani; Muksin (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of deposit interest rates on third party funds in BJB Bank, Branch Rangkasbitung. Data collected is secondary data. Data analysis techniques using simple linear regression. The results indicated that the deposit interest rate had a negative and significant effect on third party funds in BJB Bank Branch Rangkasbitung.